(untitled) (International Journal of Engineering and Computer Science, 2017)
This paper gives idea about how the nail colors, texture, shape, and pliability are useful to predict diseases. In traditional system of disease detection doctors observe the nails of patients and then predict the disease. It requires more time and the prediction is not much accurate, because human eyes cannot differentiate the slight change in color. Various image analysis and digital image processing technique such as Image acquisition, Image pre-processing, Segmentation, Feature extraction etc are used to identify features of nail. Generally Smooth, pink and shiny nails indicate healthy human. This paper has reviewed the various techniques used to process the nail images for disease detection.